Do Resources Support the Success of Education Curriculum? Vocational School Context at Sinjai - Umar; Nurfaizah; Firdaus, Muh. Adnan; Muhlisa, Nurul; Rahmawati; Syuhaemi; Harmilawati (JLE: Journal of Literate of English Education Study Program, 2022)
This research sets the goal to identify and document the resources supporting the success of the 2013 curriculum at SMKN 2 Sinjai and to question these contributions based on empirical facts. There are many factors and even cases related to various supporting resources, but in different contexts and places. Qualitative data were collected descriptively-exploratively as an option to see events in objects. The criteria for contributing informants were principals, related teachers and other educators and were selected by purposive sampling. Interview, observation and document review techniques were combined to obtain data and ensured validity through triangulation techniques. The collected data was then analyzed by identified, grouped, verified, synthesized, and compared. Interpretive analysis reveals that various factors and resources have contributed to the success of the learning curriculum such as representative facilities and infrastructure, managerial principals, resource competence and educator collaboration, educator learning management, utilization of learning resources, and use of learning strategies and models. These findings can contribute and have implications for the management of educational curriculum implementation and in different educational institutions.